Efficient Induction of Cytotoxic T Cells by Viral Vector Vaccination Requires STING-Dependent DC Functions - Barnowski, Cornelia; Ciupka, Gregor; Tao, Ronny; Jin, Lei; Busch, Dirk H.; Tao, Sha; Drexler, Ingo (Frontiers in Immunology, 2020)
Modified Vaccinia virus Ankara (MVA) is an attenuated strain of vaccinia virus and currently under investigation as a promising vaccine vector against infectious diseases and cancer. MVA acquired mutations in host range and immunomodulatory genes, rendering the virus deficient for replication in most mammalian cells. MVA has a high safety profile and induces robust immune responses. However, the role of innate immune triggers for the induction of cytotoxic T cell responses after vaccination is incompletely understood. Stimulator of interferon genes (STING) is an adaptor protein which integrates signaling downstream of several DNA sensors and therefore mediates the induction of type I interferons and other cytokines or chemokines in response to various dsDNA viruses. Since the type I interferon response was entirely STING-dependent during MVA infection, we studied the effect of STING on primary and secondary cytotoxic T cell responses and memory T cell formation after MVA vaccination in STING KO mice. Moreover, we analyzed the impact of STING on the maturation of bone marrow-derived dendritic cells (BMDCs) and their functionality as antigen presenting cells for cytotoxic T cells during MVA infection in vitro. Our results show that STING has an impact on the antigen processing and presentation capacity of coventionel DCs and played a crucial role for DC maturation and type I interferon production. Importantly, STING was required for the induction of efficient cytotoxic T cell responses in vivo, since we observed significantly decreased short-lived effector and effector memory T cell responses after priming in STING KO mice. These findings indicate that STING probably integrates innate immune signaling downstream of different DNA sensors in DCs and shapes the cytotoxic T cell response via the DC maturation phenotype which strongly depends on type I interferons in this infection model. Understanding the detailed functions of innate immune triggers during MVA infection will contribute to the optimized design of MVA-based vaccines.